Norwegian Courts and Sámi Law - Øyvind Ravna (Arctic Review on Law and Politics, 2021)
For decades, Norway has been viewed as a role model when it comes to safeguarding Sámi rights as an Indigenous people in the Nordic Countries. Among other reasons, this is because Norway is the only country with a Sámi population that has ratified ILO Convention No. 169. Also, Norway has adopted a particular land law where one of the purposes is to survey Sámi rights to land and water. It is also said that Norway has worked actively to ensure adoption of the 2007 UN Declaration on the Rights of Indigenous Peoples. Norway has gained international recognition for this work, among others from former UN Special Rapporteur on the Rights of Indigenous People James Anaya, who in his report on the situation of the Sámi people in Norway, Sweden and Finland, stated that Norway, since passing the Finnmark Act 2005, has set an important example for the other Nordic countries (para 44).